(untitled) (Journal of Scientific Research, 2023)
Thiosemicarbazones are class of compounds which are obtained by the condensation of thiosemicarbazide with carbonyl compounds. The transition metal complexes of thiosemicarbazones are widely considered due to their broad spectrum of biological activities such as antibacterial, antitumor and antifungal activities. In present research work a series of four novel Cu(II) aryl thiosemicarbazones complexes having the general composition [Cu(L1)2Cl2], [Cu(L2)2Cl2], [Cu(L3)2Cl2] and [Cu(L4)2Cl2]where L1= 4-nitroacetophenone thiosemicarbazones (4NAT), L2 = 3-nitrobenzaldehyde thiosemicarbazone (3NBT), L3 = 4-hydroxybenzaldehyde thiosemicarbazone (4HBT) and L4 = 4-aminoacetophenone thiosemicarbazone (4AAT) have been synthesized by the reaction of thiosemicarbazide with substituted aromatic aldehydes and ketones by conventional heating as well as microwave irradiations method followed by complexation with Cu(II) metal. The synthesized compounds have been characterised by elemental analysis, melting point determination, FTIR, UV-visible spectral analysis. Thiosemicarbazone ligands behave as bidentate ligand and forms octahedral complexes with Cu(II). The synthesized ligands and their new metal complexes have been screened in vitro for antibacterial activity against Escherichia coli, Staphylococcus aureus and Bacillus subtilis bacteria. The result shows that all the Cu(II) complexes are potent antibacterial agents against these bacteria.